Pattern of Neuropsychiatric Illnesses in Geriatric Population: An Outpatient Study Report (Journal of Psychiatrists' Association of Nepal, 2017)
Introduction: Few studies are available till date on the pattern of neuro-psychiatric illnesses in geriatric population in Nepal.Objective: The study was aimed to know the demographic and clinical profiles of geriatric outpatients in our neuropsychiatry OPD.Method: This study was conducted at the Department of Psychiatry, Universal College of Medical Sciences-Teaching Hospital (UCMS-TH), Bhairahawa, Nepal. We screened through our ‘OPD case registrar’, which maintains few demographic and clinical data of all the new and old cases registered daily in the OPD. Socio-demographic and clinical data of all the patients in the age of 60 years and above were noted in a data sheet specially designed for the present study. This is a retrospective study by chart review. Descriptive analysis of these data were undertaken by using simple frequency distribution.Result: During the one year study period total number of new patients registered were 3711. Two-hundred and fifty-seven (6.9%) among them were in the geriatric age group (≥60 years age). Psychoses form the biggest diagnostic entity with 71 patients (27.6%) followed by Depression in 39 patients (15.2%), Chronic headache in 33 (12.8%), Alcohol Dependence Syndrome in 27 (10.5%), Anxiety disorders in 25 (9.7%) and Dementia in 23 (8.9%) elderly patients. We also recorded 11 patients (4.3%) with symptoms of Mania. ‘Psychosis’ and ‘Depression’, were more represented amongst female elderly while ‘Alcohol dependence’ and ‘Mania’ and were more frequently prevailed among male elderly patient population.Conclusion: Present study is expected to add some more light on this sub-specialty in Psychiatry and hope to induce more interest among young researchers to carry our further research among geriatric psychiatric patients in Nepal.